2017
DOI: 10.1038/s41598-017-08376-1
|View full text |Cite
|
Sign up to set email alerts
|

The study of electronic nematicity in an overdoped (Bi, Pb)2Sr2CuO6+δ superconductor using scanning tunneling spectroscopy

Abstract: The pseudogap (PG) state and its related intra-unit-cell symmetry breaking remain the focus in the research of cuprate superconductors. Although the nematicity has been studied in Bi2Sr2CaCu2O8+δ, especially underdoped samples, its behavior in other cuprates and different doping regions is still unclear. Here we apply a scanning tunneling microscope to explore an overdoped (Bi, Pb)2Sr2CuO6+δ with a large Fermi surface (FS). The establishment of a nematic order and its real-space distribution is visualized as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…In addition, we observed orbital nematicity, due to an asymmetry in the charge distribution between the p x and p y orbitals in agreement with results from STM experiments. 43,44 Focusing on the copper d-orbital the nematicity observed with Resonant X-ray Scattering in the striped phase of (La,M) 2 CuO 4 45 was also found in our analysis. Using 8×8 clusters, and by focusing on the absolute value of the nematic order parameter, we unveiled tendencies towards half-filled stripes even in square clusters: the average over long runs appears featureless but by using absolute values it can be shown that there is nematicity even in square clusters.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, we observed orbital nematicity, due to an asymmetry in the charge distribution between the p x and p y orbitals in agreement with results from STM experiments. 43,44 Focusing on the copper d-orbital the nematicity observed with Resonant X-ray Scattering in the striped phase of (La,M) 2 CuO 4 45 was also found in our analysis. Using 8×8 clusters, and by focusing on the absolute value of the nematic order parameter, we unveiled tendencies towards half-filled stripes even in square clusters: the average over long runs appears featureless but by using absolute values it can be shown that there is nematicity even in square clusters.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the previously mentioned STM experiments 43,44 did not observe nematicity associated with the d orbitals. However, the results of Resonant X-ray Scattering in the stripe phase of (La,M) 2 CuO 4 (M =Sr, Ba, Eu, or Nd) 45 reported nematicity in the d orbitals.…”
Section: B Nematicitymentioning
confidence: 48%
See 1 more Smart Citation
“…STM measurements were carried out in a commercial ultrahigh-vacuum system [32,[37][38][39]. An electrochemically etched tungsten tip was treated with field emission on a single crystal of the Au (111) surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The existence of CDWs in high-T c oxides has been recently confirmed by various experimental methods, including direct scanning-tunnel-microscopy (STM) and x-ray diffraction ones. In particular, CDWs were revealed in holedoped La 2−xBax CuO 4 [49], YBa 2 Cu 3 O 7−δ [16,[50][51][52][53][54][55][56][57][58][59][60], Bi 2 Sr 2−xLax CuO 6+δ [61], (Bi, Pb) 2 Sr 2 CuO 6+δ [62], and Bi 2 Sr 2 CaCuO 8+δ [16,56,[63][64][65][66] cuprates, as well as in electron-doped Nd 2−x Ce x CuO 4 ones [67]. The observed CDWs have either a unidirectional (stripe-like) or a bidirectional (checkerboard-like) structure.…”
Section: Introductionmentioning
confidence: 99%